PENERAPAN PERJANJIAN KONTRAK DALAM JUAL BELI E-COMMERCE - Anis Ellysia; Wika Milatul Jannah; Lucky Dafira Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Contract policy in e-commerce buying and selling, which then shows how important consumer protection is in subsequent transactions. With the advancement of technology, e-commerce has become an indispensable part of everyday life, offering convenience and efficiency. However, challenges such as fraud, non-conformity of goods, and information security remain. This study uses a qualitative approach to analyze the dynamics of law and consumer protection in the context of e-commerce, and provides recommendations to improve justice and legal certainty for the parties involved.